Hindī ekāṅkī aura Ḍô. [i.e. Ḍôkṭara] Rāmakumāra Varmā - Śrīvāstava, Pushpalatā, 1942- (Parāga Prakāśana, 1979)
On the development of the Hindi one-act play and the contributions of Ram Kumar Varma, b. 1905; a study.